Conceptualization and Actualization of Law Living in Society on The Design of The Criminal Law Law Related to The Establishment of National Law - Rika Kurniasari A (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Good law is law that is in accordance with the law that lives in society (the living law) and is in accordance with the reflection of the values that apply in that society. On progress, the main regulations of criminal law in the future which have been formulated in theRKUHP hasaccommodate the living law as part of positive law as stated in Article 2 paragraph (1) RKUHP. This research analyzes thethe conception of the rule of law that lives in society as regulated in Article 2 Paragraph (1) of the RKUHP in the context of the formation of national law. The results of the study showthat dthe implication of the principle of material legality in the RKUHP is wrong. If the formulation of the principle of material legality in Article 2 paragraph (1) of this RKUHP is not abolished and is still maintained, then the Indonesian legal system will experience a setback. Therefore, the enactment of the living law in society (the living law) in the national legal system is sufficient only to serve as the basis for the formation of national law.